2022
DOI: 10.2903/j.efsa.2022.7076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of animal diseases caused by bacteria resistant to antimicrobials: kept fish species

Abstract: In this Opinion, the antimicrobial‐resistant bacteria responsible for transmissible diseases that constitute a threat to the health of certain kept fish species have been assessed. Atlantic salmon (Salmo salar), carp (Cyprinus spp.), rainbow trout (Oncorhynchus mykiss), sea bream (Sparus aurata) and tilapia (Oreochromis spp.), selected as representative of the most important fish species and production systems that are commercially reared in fresh and saltwater farms, were the focus of this assessment. The ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Treatment failure due to antimicrobial resistance (AMR) is considered one of the largest threats to human and animal health ( 1 – 6 ). Multiple studies have shown that AMR bacteria and, in some cases, antimicrobial resistance genes (ARGs) can be transferred between livestock and humans ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment failure due to antimicrobial resistance (AMR) is considered one of the largest threats to human and animal health ( 1 – 6 ). Multiple studies have shown that AMR bacteria and, in some cases, antimicrobial resistance genes (ARGs) can be transferred between livestock and humans ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%